Comparison of mouse and human cytochrome P450 mediated-drug metabolising activities in hepatic and extrahepatic microsomes. (4th March 2022) - Uehara, Shotaro; Murayama, Norie; Higuchi, Yuichiro; Yoneda, Nao; Yamazaki, Hiroshi; Suemizu, Hiroshi
Abstract: Despite the importance of mice as a preclinical species in drug testing, their hepatic and extrahepatic drug-metabolising characteristics are poorly understood. Here, we compared the P450-dependent drug oxidation activity in tissue microsomes and distribution patterns of P450 protein/mRNA between humans and mice. The activities of midazolam 1′-/4-hydroxylation in the liver and intestine and chlorzoxazone 6-hydroxylation in the liver were similar in humans and mice. The activities of coumarin 7-hydroxylation, flurbiprofen 4′-hydroxylation, and S -mephenytoin 4′-hydroxylation in the liver were higher in humans than in mice. The activities of 7-ethoxyresorufin O -deethylation in the liver, 7-pentoxyresorufin O -depentylation in the lung/liver/intestine, bufuralol 1′-hydroxylation in the liver/intestine, propafenone 4′-hydroxylation in liver/intestine, and diazepam N -demethylation in the liver/intestine were higher in mice than in humans. CYP1A2/2E1 mRNAs were mainly expressed in the livers of humans and mice. Cyp2b9/2b10 mRNAs were abundant in the mouse lung/liver/intestine, but CYP2B6 was mainly expressed in the human liver. CYP2C/2D/3A mRNAs were expressed in the liver and intestine, with the respective proteins detected in tissue microsomes of both humans and mice. These information on P450-dependent drug-metabolising characteristics in hepatic and extrahepatic tissues is useful to understand the similarities and differences between humans and mice in drug metabolism.